2016
DOI: 10.1038/srep32304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anatomical and Nonanatomical Hepatectomy for Colorectal Liver Metastasis: A Meta-Analysis of 5207 Patients

Abstract: It remains unclear whether hepatectomy for colorectal liver metastasis (CRLM) should be performed as anatomical resection (AR) or nonanatomical resection (NAR). The aim of this study is to compare the short- and long-term outcomes of AR and NAR for CRLM. PubMed, Web of Science, EMBASE and the Cochrane Library were systematically searched to identify eligible studies. Twenty one studies involving 5207 patients were analyzed: 3034 (58.3%) underwent AR procedure and 2173 (41.7%) underwent NAR procedure. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…In contrast, several studies suggest that NAR provides similar oncologic outcomes compared with formal AR with the advantage of decreasing perioperative morbidity among patients with colorectal liver metastasis. 5 In the current study, we present one of the largest series comparing the oncologic outcomes of patients with NELM following AR and NAR. In concordance with previous studies, we found that an R1 resection margin status significantly decreased OS and RFS, while the amount of estimated liver involvement and the presence of bilateral liver disease did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, several studies suggest that NAR provides similar oncologic outcomes compared with formal AR with the advantage of decreasing perioperative morbidity among patients with colorectal liver metastasis. 5 In the current study, we present one of the largest series comparing the oncologic outcomes of patients with NELM following AR and NAR. In concordance with previous studies, we found that an R1 resection margin status significantly decreased OS and RFS, while the amount of estimated liver involvement and the presence of bilateral liver disease did not.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of colorectal liver metastases (CRLM), parenchyma-preserving NAR has been shown to decrease morbidity without sacrificing oncologic effectiveness. 5 However, for certain subtypes of CRLM, NAR has been associated with worse disease free survival 6 and inferior oncologic outcomes. 7 For NELM, multiple studies have demonstrated improved survival when comparing surgery with medical or catheter-based therapies 8,9 and reasonable survival even when only debulking hepatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…31,47 Liver-sparing hepatectomy is considered the gold standard for curative resection in colorectal liver metastases (CLM). 38,48,49 Along with surgery, chemotherapy is an important aspect in the management of CLM, as it may downstage and increase resectability of previously inoperable lesions. 47,50 Chemotherapy-induced liver injury including steatosis, steatohepatitis and sinusoidal obstruction syndrome can make it more challenging for major liver surgery requiring extensive resections.…”
Section: Discussionmentioning
confidence: 99%
“…Eight patients encompassing 10 lesions were included in the study (Table 2). The mean liver volume was 2,050.97 cm 3 3 (SD, 35.67)] when compared to DIBH-SRS [150.12 cm 3 (SD, 81.43), p = 0.002] or FB-SRS [306.13 cm 3 (SD, 128.75), p = 0.002; Figure 1]. For the remaining constraints, IORT was compared with DIBH-SRS and FB-SRS, and the results are detailed as follows.…”
Section: Patients and Planning Featuresmentioning
confidence: 98%